Mapeamento e perfil da mortalidade materna por microrregião de saúde do Ceará: 1997 - 2008 - Carvalho, Julia Maria de Oliveira (2011)
This work aims to map and to trace the profile of maternal mortality by micro-regions of health in the state of Ceará in the period from 1997 to 2008, according to the database of SESA-1997-2008 and SIM- maternal mortality system- M.S. Based on the LQ (location quotient) that works as situation indicator, it is possible to qualify the maternal mortality in terms of the demand and supply of health services. The statistics that represent health demand are: percentage of death in mothers in a gestational age risk group and percentage of death by avoidable causes. The statistics that represent health supply are: percentage of death with hospital care and percentage of death where the mother was transferred to other health units. The variation of the percentage of death with proper prenatal appointments during a women’s pregnancy is directly related to the demand and supply of health services. In summary, the maternal mortality among the micro-regions of Ceará is still high and presents a big regional variation. The micro-regions of Caucaia and Crateús stand out among the others for presenting worst situation in the demand as well as in the supply of health services.